2022
DOI: 10.17977/um044v7i22022p18-24
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Edukasi Pemberian Makan Balita dengan Metode Emotional Demonstration dan Metode Ceramah terhadap Pengetahuan dan Sikap Ibu Balita di RT 06 RW 08 Kelurahan Keputih Kota Surabaya

Abstract: Undernutrition under five years old has a variety of health risks. In Surabaya, the SSGI 2021 report that underweight cases were 16,6 percent. One of the causes of nutritional problems for toddlers is the behavior of mothers in feeding toddlers which will affect the growth and development of toddlers. The right educational method is needed to change behavior, namely Emotional Demonstration (Emo Demo). This study aimed to analyze the differences in emo demo education and lectures on the knowledge and attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Other research that is also in line is research conducted by [21] which concluded that there were differences in the attitudes of mothers of toddlers in Keputih Village before and after being given education about feeding toddlers using the emo demo method. Other research also obtained results that there were differences in the attitudes of baduta mothers towards education about MP-Asi after using the emo demo method in Trenggalek Regency [22].…”
Section: B Attitudementioning
confidence: 63%
“…Other research that is also in line is research conducted by [21] which concluded that there were differences in the attitudes of mothers of toddlers in Keputih Village before and after being given education about feeding toddlers using the emo demo method. Other research also obtained results that there were differences in the attitudes of baduta mothers towards education about MP-Asi after using the emo demo method in Trenggalek Regency [22].…”
Section: B Attitudementioning
confidence: 63%